1989
DOI: 10.1063/1.528456
|View full text |Cite
|
Sign up to set email alerts
|

The quantum relativistic two-body bound state. II. The induced representation of SL(2,C)

Abstract: It was shown in I [J. Math. Phys. 30, 66 (1989)] that the eigenfunctions for the reduced motion of the quantum relativistic bound state with O(3,1) symmetric potential have support in an O(2,1) invariant subregion of the full spacelike region. They form irreducible representations of SU(1,1) [in the double covering of O(2,1)] parametrized by the unit spacelike vector nμ, taken in I as the direction of the z axis (the spectrum is independent of this choice), for which this O(2,1) is the stabilizer. Lorentz tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 4 publications
0
43
0
Order By: Relevance
“…Perhaps most significantly, while defining the system in an unconstrained 8D phase space relaxes the a priori mass shell relationẋ 2 = c 2 and thus permits classical trajectories that reverse the direction of their time evolution, it also eliminates reparameterization invariance. This is because the mass shell constraint and reparameterization invariance are related features of a Lagrangian that is homogeneous of first degree in the velocities, which is not the case for (8). Moreover, in Stueckelberg-Horwitz-Piron (SHP) electrodynamics, the evolution parameter τ cannot be identified as the proper time of the motion, but is a dynamical quantity proportional to it through…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps most significantly, while defining the system in an unconstrained 8D phase space relaxes the a priori mass shell relationẋ 2 = c 2 and thus permits classical trajectories that reverse the direction of their time evolution, it also eliminates reparameterization invariance. This is because the mass shell constraint and reparameterization invariance are related features of a Lagrangian that is homogeneous of first degree in the velocities, which is not the case for (8). Moreover, in Stueckelberg-Horwitz-Piron (SHP) electrodynamics, the evolution parameter τ cannot be identified as the proper time of the motion, but is a dynamical quantity proportional to it through…”
Section: mentioning
confidence: 99%
“…in the argument of nonrelativistic scalar potentials, Horwitz et al found solutions for relativistic generalizations of the standard central force problems, including quantum mechanical potential scattering and bound states [4][5][6][7][8]. Examination of radiative transitions [9][10][11] associated with these bound states suggests that the scalar interaction V is required along with the four-vector potential A µ in order to account for known phenomenology.…”
Section: mentioning
confidence: 99%
“…The connection with Maxwell theory enlarges on Stueckelberg's observation in (13). Under the conditions j 5 → 0 and f 5µ → 0, pointwise in x as τ → ±∞, integration of (24) over τ , called concatenation of events into a worldlines [9], recovers the relations…”
Section: Concatenationmentioning
confidence: 99%
“…Within this framework, solutions have been found for the generalizations of the standard central force problem, including potential scattering [11] and bound states [12,13]. Examination of radiative transitions [14], in particular the Zeeman [15] and Stark effects [16], indicate that all five components of the gauge potential are necessary for an adequate explanation of observed phenomenology.…”
Section: Implications For the Parameterized Mechanicsmentioning
confidence: 99%
“…The Relativistic Harmonic Oscillator is probably the simplest relativistic system containing bound states, yet it exhibits the typical problems of Relativistic Quantum Mechanics. Many papers have been devoted to the solution of this relativistc system [1,2,3,4,5] although the first question is probably to define what we understand by a Relativistic Harmonic Oscillator.…”
Section: Introductionmentioning
confidence: 99%